Droplet impingement and performance from droplet generator - Abdul Aziz Mohamed Azlee (2014)
This Final Year Project (FYP) report covers the summary of literature review done, the design of the droplet generator system testing rig, and also the results and analysis of various experiments done on the droplet generator system to determine its performance and observations of droplet impingement on surfaces. The optimal frequency for each pinhole diameter has been determined from the droplet observation experiment. It can be seen that with an increase in the frequency, the distance between droplets will become smaller and a slight reduction in droplet size. Also, it is imperative to use a hi-speed camera to observe the droplet impingement. The droplet impinged on the surface underwent deposition, which verifies the outcome from an experiment conducted in an academic journal, presented by Gail Duursma et al. (2009). For droplet impingement on heated plate, the droplet underwent partial levitation due to reduction of its mass from evaporation, which also verifies the outcome from an experiment conducted in an academic journal, presented by Satish G. Kandlikar (2001).